Mass. Gen. Laws ch. 240 § 1 (1837) - (:unkn) unknown (General Publisher, 1837)
Enrolled every able bodied white male citizen resident between eighteen to forty-five into the miltiia except idiots, lunatics, common drunkards, vagabonds, paupers, persons convicted of any infamous crime.
--
Keywords: ARMED FORCES